Positive film structure of post-texturing type back contact battery and preparation method of positive film structure

By adopting the positive film structure of the back-feather-contact battery on the front of the solar cell and preparing the film layer by using the low-temperature and low-pressure process, the problem of poor uniformity of the front film layer is solved, and the light absorption conversion efficiency of the solar cell is significantly improved.

CN119521857APending Publication Date: 2025-02-25POPSOLAR TECHNOLOGY (JIANGMEN) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411700510.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The efficiency of existing solar cells is mainly due to the poor uniformity of the front film layer, which affects the absorption and conversion of light.

Method used

The positive film structure of the rear velvet-making back contact battery is adopted, including a silicon oxide pretreatment film layer, a silicon nitride low film layer, a silicon nitride oxide film layer and a silicon nitride uppermost layer and other film layers arranged from bottom to top. It is prepared by a low-temperature and low-pressure process to adjust the film layer thickness to improve uniformity.

Benefits of technology

A more uniform film layer structure is achieved, which improves the life of the nucleus and passivation value, reduces the reflectance and improves the absorption and conversion efficiency of light.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119521857A_ABST
    Figure CN119521857A_ABST
Patent Text Reader

Abstract

The invention provides a front film structure of a rear texturing type back contact battery and a preparation method of the front film structure, and belongs to the technical field of solar batteries. The positive film structure comprises a silicon oxide pretreatment film layer 1, a first silicon nitride low film layer 2, a second silicon nitride low film layer 3, a first silicon oxynitride film layer 4, a silicon nitride uppermost layer 5, a second silicon oxynitride film layer 6, a third silicon oxynitride film layer 7 and a silicon oxide covering layer 8 which are sequentially arranged on the front surface of a substrate from bottom to top. Different film layers are prepared by adopting a low-temperature and low-pressure process, and the thickness of the film layers is adjusted, so that the obtained film layers are more uniform in structure, the minority carrier lifetime and the passivation value are improved to a certain extent, the reflectivity is lower, and light absorption and conversion are better realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solar cells, and in particular to a positive film structure of a post-texture-made back-contact cell and a preparation method thereof. Background Art

[0002] BC cell, which refers to the back contact cell, is an advanced design used to improve the efficiency of solar cells. Its core design concept is to place all the metal electrodes of the cell on the back of the cell, so as to ensure that the front of the cell is not blocked by any metal grid lines, thereby maximizing the area of ​​the cell that absorbs sunlight, reducing optical losses, and improving the photoelectric conversion efficiency. The feature of no grid lines on the front makes its front appearance requirements higher. However, due to the basic structural framework of the technical route of the cell, the lack of grid lines on the front makes its light absorption area larger, the light conversion is better, and the requirements for the uniformity of the front film layer are more stringent. Therefore, it is of great significance to study a positive film structure of a post-velvet back contact cell and its preparation method, so that the positive film is more uniform and more conducive to improving the efficiency of solar cells. Summary of the invention

[0003] The object of the present invention is to provide a positive film structure of a post-textured back contact cell and a preparation method thereof, so as to solve the problem of low efficiency of solar cells in the prior art.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The present invention provides a positive film structure of a post-textured back-contact battery, wherein the positive film structure comprises a silicon oxide pretreatment film layer 1, a first silicon nitride low film layer 2, a second silicon nitride low film layer 3, a first silicon oxynitride film layer 4, a silicon nitride uppermost layer 5, a second silicon oxynitride film layer 6, a third silicon oxynitride film layer 7, and a silicon oxide covering layer 8, which are sequentially arranged on the front side of a substrate from bottom to top.

[0006] Preferably, the thickness of the silicon oxide pretreatment film layer 1 is 1-2 nm.

[0007] Preferably, the thickness of the first silicon nitride low film layer 2 is 6-8 nm; the thickness of the second silicon nitride low film layer 3 is 8-14 nm.

[0008] Preferably, the thickness of the first silicon oxynitride film layer 4 is 2-3 nm; the thickness of the uppermost silicon nitride layer 5 is 34-36 nm.

[0009] Preferably, the second silicon oxynitride film layer 6 has a thickness of 4-5 nm; and the third silicon oxynitride film layer 7 has a thickness of 5-7 nm.

[0010] Preferably, the thickness of the silicon oxide capping layer 8 is 3-4 nm.

[0011] The present invention also provides a method for preparing the positive film structure of the above-mentioned post-textured back-contact battery, wherein a silicon oxide pretreatment film layer 1, a first silicon nitride low film layer 2, a second silicon nitride low film layer 3, a first silicon oxynitride film layer 4, a silicon nitride top layer 5, a second silicon oxynitride film layer 6, a third silicon oxynitride film layer 7, and a silicon oxide covering layer 8 are deposited in sequence from bottom to top on the front side of the substrate to obtain a positive film structure.

[0012] Preferably, the deposition is performed using plasma enhanced chemical vapor deposition technology; the temperature of the deposition is independently 450-490° C., and the pressure is independently 1000-1200 MPa.

[0013] Beneficial effects of the present invention:

[0014] The present invention adopts a low-temperature and low-pressure process to prepare different film layers. Combined with the adjustment of the film layer thickness, the obtained film layer structure is more uniform, the minority carrier lifetime and passivation value are improved to a certain extent, the reflectivity is lower, and the absorption and conversion of light is better achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 Schematic diagram of the positive film structure of the present invention, wherein 1 is a silicon oxide pretreatment film layer, 2 is a first silicon nitride lower film layer, 3 is a second silicon nitride lower film layer, 4 is a first silicon oxynitride film layer, 5 is a silicon nitride uppermost layer, 6 is a second silicon oxynitride film layer, 7 is a third silicon oxynitride film layer, and 8 is a silicon oxide capping layer;

[0016] Figure 2 Schematic diagram of the positive film structure of comparative example 1, wherein 9 is a first silicon nitride high-refractive film layer, 10 is a second silicon nitride medium-refractive film layer, and 11 is a third silicon nitride medium-refractive film layer. DETAILED DESCRIPTION

[0017] The present invention provides a positive film structure of a post-textured back-contact battery, wherein the positive film structure comprises a silicon oxide pretreatment film layer 1, a first silicon nitride low film layer 2, a second silicon nitride low film layer 3, a first silicon oxynitride film layer 4, a silicon nitride uppermost layer 5, a second silicon oxynitride film layer 6, a third silicon oxynitride film layer 7, and a silicon oxide covering layer 8, which are sequentially arranged on the front side of a substrate from bottom to top.

[0018] In the present invention, the thickness of the silicon oxide pretreatment film layer 1 is 1-2 nm, preferably 1 nm.

[0019] In the present invention, the thickness of the first silicon nitride low film layer 2 is 6-8 nm, preferably 6 nm; the thickness of the second silicon nitride low film layer 3 is 8-14 nm, preferably 9-13 nm, and more preferably 10-12 nm.

[0020] In the present invention, the thickness of the first silicon oxynitride film layer 4 is 2-3 nm, preferably 2 nm; the thickness of the uppermost silicon nitride layer 5 is 34-36 nm, preferably 35 nm.

[0021] In the present invention, the thickness of the second silicon oxynitride film layer 6 is 4-5 nm, preferably 5 nm; the thickness of the third silicon oxynitride film layer 7 is 5-7 nm, preferably 7 nm.

[0022] In the present invention, the thickness of the silicon oxide capping layer 8 is 3-4 nm, preferably 3 nm.

[0023] The present invention also provides a method for preparing the positive film structure of the above-mentioned post-textured back-contact battery, wherein a silicon oxide pretreatment film layer 1, a first silicon nitride low film layer 2, a second silicon nitride low film layer 3, a first silicon oxynitride film layer 4, a silicon nitride top layer 5, a second silicon oxynitride film layer 6, a third silicon oxynitride film layer 7, and a silicon oxide covering layer 8 are deposited in sequence from bottom to top on the front side of the substrate to obtain a positive film structure.

[0024] In the present invention, the deposition is carried out by plasma enhanced chemical vapor deposition technology; the temperature of the deposition is independently 450-490° C., preferably 460-480° C., and the pressure is independently 1000-1200 MPa, preferably 1100 MPa.

[0025] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0026] Example 1

[0027] On a velvet silicon-based substrate, a silicon oxide pretreatment film layer 1, a first silicon nitride low film layer 2, a second silicon nitride low film layer 3, a first silicon oxynitride film layer 4, a silicon nitride uppermost layer 5, a second silicon oxynitride film layer 6, a third silicon oxynitride film layer 7, and a silicon oxide capping layer 8 are deposited in sequence from bottom to top on the front side of the substrate at a temperature of 480°C and a pressure of 1100MPa using plasma enhanced chemical vapor deposition technology to obtain a positive film structure-1, wherein the thickness of the silicon oxide pretreatment film layer 1 is 1nm, the thickness of the first silicon nitride low film layer 2 is 6nm, the thickness of the second silicon nitride low film layer 3 is 10nm, the thickness of the first silicon oxynitride film layer 4 is 2nm, the thickness of the silicon nitride uppermost layer 5 is 35nm, the thickness of the second silicon nitride film layer 6 is 5nm, the thickness of the third silicon oxynitride film layer 7 is 7nm, and the thickness of the silicon oxide capping layer 8 is 3nm.

[0028] Example 2

[0029] On a velvet silicon-based substrate, a silicon oxide pretreatment film layer 1, a first silicon nitride low film layer 2, a second silicon nitride low film layer 3, a first silicon oxynitride film layer 4, a silicon nitride uppermost layer 5, a second silicon oxynitride film layer 6, a third silicon oxynitride film layer 7, and a silicon oxide covering layer 8 are deposited in sequence from bottom to top on the front side of the substrate at a temperature of 450°C and a pressure of 1200MPa by plasma enhanced chemical vapor deposition technology to obtain a positive film structure-2, wherein the thickness of the silicon oxide pretreatment film layer 1 is 2nm, the thickness of the first silicon nitride low film layer 2 is 8nm, the thickness of the second silicon nitride low film layer 3 is 14nm, the thickness of the first silicon oxynitride film layer 4 is 3nm, the thickness of the silicon nitride uppermost layer 5 is 36nm, the thickness of the second silicon nitride film layer 6 is 4nm, the thickness of the third silicon oxynitride film layer 7 is 5nm, and the thickness of the silicon oxide covering layer 8 is 4nm.

[0030] Example 3

[0031] On a velvet silicon-based substrate, a silicon oxide pretreatment film layer 1, a first silicon nitride low film layer 2, a second silicon nitride low film layer 3, a first silicon oxynitride film layer 4, a silicon nitride uppermost layer 5, a second silicon oxynitride film layer 6, a third silicon oxynitride film layer 7, and a silicon oxide covering layer 8 are deposited in sequence from bottom to top on the front side of the substrate at a temperature of 470°C and a pressure of 1000MPa by plasma enhanced chemical vapor deposition technology to obtain a positive film structure-3, wherein the thickness of the silicon oxide pretreatment film layer 1 is 2nm, the thickness of the first silicon nitride low film layer 2 is 7nm, the thickness of the second silicon nitride low film layer 3 is 8nm, the thickness of the first silicon oxynitride film layer 4 is 3nm, the thickness of the silicon nitride uppermost layer 5 is 34nm, the thickness of the second silicon nitride film layer 6 is 4nm, the thickness of the third silicon oxynitride film layer 7 is 6nm, and the thickness of the silicon oxide covering layer 8 is 4nm.

[0032] Comparative Example 1

[0033] A first layer of silicon nitride high refractive film is deposited on the front side of the textured silicon-based substrate. The process parameters are: silane flow rate is 1100 sccm, ammonia flow rate is 7000 sccm, temperature is controlled at 550°C, pressure is 1750 mtorr, deposition time is 100 s, the thickness of the first layer of silicon nitride high refractive film is 10 nm, and the refractive index is 2.2-2.5;

[0034] A second silicon nitride medium refractive film layer is deposited on the first silicon nitride high refractive film layer, and the process parameters are: silane flow rate is 1100sccm, ammonia flow rate is 7000sccm, temperature is controlled at 550°C, pressure is 1750mtorr, deposition time is 200s, the thickness of the second silicon nitride medium refractive film layer is 15nm, and the refractive index is 2.0-2.1;

[0035] A third layer of silicon nitride medium refractive film is deposited on the second layer of silicon nitride medium refractive film. The process parameters are: silane flow rate is 800sccm, ammonia flow rate is 7400sccm, temperature is controlled at 530°C, pressure is 1800mtorr, deposition time is 440s, thickness of the third layer of silicon nitride medium refractive film is 40nm, refractive index is 1.7-1.9, and positive film structure-4 is obtained.

[0036] Performance Test:

[0037] (1) Passivation test:

[0038] The original silicon wafer was selected and placed in a cleaning basket for alkaline polishing to prepare a test piece; the test piece was deposited with a 4-7 nm aluminum oxide film on both sides by atomic layer deposition technology, and then double-sided deposition was performed according to the method of Example 1 and the method of Comparative Example 1, respectively. After the deposition was completed, sintering was performed at a temperature of 700-800° C. Finally, the prepared samples were tested in a passivation tester (WCT-120). Five samples were tested in Example 1 and four samples were tested in Comparative Example 1. The results are shown in Table 1:

[0039] Table 1 Passivation test data

[0040]

[0041] (2) Ellipsometer test: According to the preparation method of Example 1 of the present invention and the preparation method of Comparative Example 1, the suede silicon-based substrate was placed in a boat to prepare the test sample, and the sample was taken in the process boat by taking the film from the outside page to the inside page of the boat according to the temperature zone. After sampling, the sample was tested and recorded on the ellipsometer. The test results are shown in Table 2 and Table 3:

[0042] Table 2 Ellipsometer test data of Example 1

[0043]

[0044]

[0045] Table 3 Ellipsometer test data of comparative example 1

[0046]

[0047]

[0048] By comparing Table 2 and Table 3, it can be seen that the uniformity of the positive film structure prepared in Example 1 is 3%, and the uniformity of the positive film structure prepared in Comparative Example 1 is 6%, which indicates that the positive film structure prepared in the present invention is more uniform.

[0049] (4) Electrical performance test:

[0050] The electrical performance of the back contact battery with the positive film structure of Example 1 and the back contact battery with the positive film structure of Comparative Example 1 were tested, with 2 samples tested for each. The results are shown in Table 4:

[0051] Table 4 Electrical performance test results

[0052] serial number quantity Eta Uoc Isc FF Comparative Example 1-1 800 25.32 0.7129 14.44 81.27 Comparative Example 1-2 756 25.31 0.7172 14.40 81.58 Example 1-1 784 25.54 0.7163 14.64 81.09 Example 1-2 765 25.56 0.7175 14.64 81.02

[0053] It can be seen from Table 4 that the Eta and Isc of the back contact battery prepared using the positive film structure of Example 1 are higher than those of Comparative Example 1.

[0054] (3) Reflectivity test results: The reflectivity of the suede silicon-based substrate of Example 1 and Comparative Example 1 and the positive film prepared on the suede substrate was tested by a reflectometer. Three samples were tested respectively. The test results are shown in Table 5:

[0055] Table 5 Reflectivity test results

[0056]

[0057]

[0058] It can be seen from Table 5 that, compared with Comparative Example 1, Example 1 of the present invention adopts a low-temperature and low-pressure process to prepare a positive film structure on a textured substrate, which can significantly reduce the reflectivity.

[0059] It can be seen from the above embodiments that the present invention provides a positive film structure of a post-textured back contact battery and a preparation method thereof, and the positive film structure of the present invention comprises a silicon oxide pretreatment film layer 1, a first silicon nitride low film layer 2, a second silicon nitride low film layer 3, a first silicon oxynitride film layer 4, a silicon nitride top layer 5, a second silicon oxynitride film layer 6, a third silicon oxynitride film layer 7, and a silicon oxide capping layer 8, which are sequentially arranged on the front of the substrate from bottom to top. The present invention adopts a low temperature and low pressure process to prepare different film layers, and combined with the adjustment of the film layer thickness, the obtained film layer structure is more uniform, the minority carrier lifetime and passivation value are improved to a certain extent, the reflectivity is lower, and the absorption and conversion of light is better realized.

[0060] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A positive film structure of a back-textured back contact battery, characterized in that: The positive film structure comprises, arranged in order from bottom to top on the front side of the substrate, a silicon oxide pretreatment film layer (1), a first silicon nitride lower film layer (2), a second silicon nitride lower film layer (3), a first silicon oxynitride film layer (4), a silicon nitride uppermost layer (5), a second silicon oxynitride film layer (6), a third silicon oxynitride film layer (7), and a silicon oxide capping layer (8).

2. The positive film structure of the rear-textured back contact battery according to claim 1, characterized in that: The thickness of the silicon oxide pretreatment film layer (1) is 1-2 nm.

3. The positive film structure of the rear-textured back contact battery according to claim 2, characterized in that: The thickness of the first silicon nitride low film layer (2) is 6-8 nm; the thickness of the second silicon nitride low film layer (3) is 8-14 nm.

4. The positive film structure of the rear-textured back contact battery according to any one of claims 1 to 3, characterized in that: The thickness of the first silicon oxynitride film layer (4) is 2-3 nm; the thickness of the uppermost silicon nitride layer (5) is 34-36 nm.

5. The positive film structure of the rear-textured back contact battery according to claim 4, characterized in that: The thickness of the second silicon oxynitride film layer (6) is 4-5 nm; the thickness of the third silicon oxynitride film layer (7) is 5-7 nm.

6. The positive film structure of the rear-textured back contact battery according to claim 5, characterized in that: The thickness of the silicon oxide covering layer (8) is 3-4 nm.

7. The method for preparing the positive film structure of a rear-textured back-contact battery according to any one of claims 1 to 6, characterized in that: A silicon oxide pretreatment film layer (1), a first silicon nitride lower film layer (2), a second silicon nitride lower film layer (3), a first silicon oxynitride film layer (4), a silicon nitride uppermost layer (5), a second silicon oxynitride film layer (6), a third silicon oxynitride film layer (7), and a silicon oxide capping layer (8) are sequentially deposited from bottom to top on the front side of the substrate to obtain a positive film structure.

8. The method for preparing the positive film structure of the rear-textured back contact battery according to claim 5, characterized in that: The deposition is carried out by plasma enhanced chemical vapor deposition technology; the temperature of the deposition is independently 450-490° C., and the pressure is independently 1000-1200 MPa.